Crack-tip constraint effects on creep fracture - Nguyen, Ba-Nghiep; Onck, Patrick; van der Giessen, Erik (Engineering fracture mechanics, 2000)
A three-term expansion describing the crack tip fields in steady power-law creeping solids is used in a small-scale damage microstructural approach to study the initial stages of creep fracture under plane strain mode I loading conditions. These fields contain three important parameters. The first one is C ∗, which sets the loading level, and the remaining, A ∗ 2 and σ ∞, account for the constraint effect imposed by the specific geometry and loading configuration. The microstructural model incorporates a process window around the tip of the crack, which contains a large number of grains that are represented discretely by so-called grain elements. The grain boundaries are described by interface elements that incorporate the principal damage mechanisms, including cavity nucleation, diffusive-creeping cavity growth and grain boundary sliding. The process window is surrounded by a standard creeping continuum which is subject to remote boundary conditions corresponding to the crack tip fields in a steadily creeping material. Numerical results of the model are presented for a range of constraints using values of A ∗ 2 and σ ∞ that correspond to typical test specimens. The effect of crack-tip constraints is demonstrated and explained for material parameter sets that give rise to either ductile or brittle creep fracture processes.